Vascularized composite allograft deceased donation in the United States - Wida S. Cherikh; Samantha M. Noreen; Alexandra Lewis; Sarah E. Booker; Jesse Howell; Erin M. Schnellinger; Jennifer L. Wainright; Christopher C. Curran (Frontiers in Transplantation)
Vascularized composite allograft (VCA) transplantation represents a significant advancement in reconstructive surgery and offers hope to individuals who experienced congenital disorders or severe tissue injuries to restore physical appearance, function, and enhance quality of life. VCA recovery introduces complexities to conventional solid organ recovery, and there remain concerns regarding the potential impact of VCA recovery on non-VCA organs for transplant. The current retrospective study examines deceased donor characteristics and observed-to-expected (O/E) organ yield ratios for 51 VCA donors recovered in the US between July 4, 2014 and March 31, 2024, compared with a contemporary cohort of non-VCA donors recovered in 2023. Among the VCA donors, 17 donated a uterus, 15 each donated head and neck and upper limbs, 4 were abdominal wall donors, and 2 donated external male genitalia. The findings indicate that VCA donors tended to be younger (18–34 years old), predominantly White, non-Hispanic, and had no history of diabetes, along with lower weight, lower kidney donor profile index, and lower ejection fraction. The analysis revealed that VCA donors had higher observed overall organ yield than expected (O/E: 1.24, 95% CI: 1.16–1.33), with better-than-expected organ yields across VCA types. The number of deceased VCA donors in the US is still relatively small compared to the overall donor population. As the field continues to evolve and more data becomes available, further analyses need to be conducted to understand the demographics of VCA donors and the potential impact of VCA donation within the donation and transplant system.